Race, Geography, and School Choice Policy: A Critical Analysis of Detroit Students' Suburban School Choices. (January 2022) - Singer, Jeremy; Lenhoff, Sarah Winchell
The purpose of this study is to advance our thinking about race and racism in geospatial analyses of school choice policy. To do so, we present a critical race spatial analysis of Detroit students' suburban school choices. To frame our study, we describe the racial and spatial dynamics of school choice, drawing in particular on the concepts of opportunity hoarding and predatory landscapes. We find that Detroit students' suburban school choices were circumscribed by racial geography and concentrated in just a handful of schools and districts. We also find notable differences between students in different racial groups. For all Detroit exiters, their schools were significantly more segregated and lower quality than those of their suburban peers. We propose future directions for research on families' school choices as well as school and district behavior at the intersection of race, geography, and school choice policy.